Pembelajaran Matematika Dengan Strategi Writing In Perfomance Tasks (Wipt) Untuk Meningkatkan Kemampuan Menulis Matematis - junaedi, Iwan (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2010)
The problem of this paperÃÂ is mathematical writing as a part of mathematical communication aspect that has not been developed optimally for theÃÂ students. One of a teaching process to develop the studentsÃ¢â¬â¢ability in mathematical writing is Writing in Performance Tasks (WiPT) strategy. The main purpose of this paper is to investigate whether a teaching process using WiPT strategy can increaseÃÂ studentsÃ¢â¬â¢ability in mathematical writing. Key words: WiPT Strategy, mathematical writing, communication.